Exploring breast health practices of post-menopausal women: Implications to informed consent - Seaman, Kristen; Dzidic, Peta; Breen, Lauren; Saunders, C. (Sage Publications Ltd, 2016)
In light of the contention surrounding breast health practices, the research aimed to explore post-menopausal women’s experiences of such practices. Semi-structured interviews were conducted in July and August 2015 with 13 Australian women aged 54–74 years. Data were analysed thematically. Participants deemed their engagement with breast health practices as the ‘right’ thing. However, engaging in these ‘right’ practices appeared to be fostered by misconceptions. The findings suggest that women may not be making evidence-informed decisions to engage in breast screening; identify contemporary barriers to promoting informed decisions; and may inform information pertinent to breast screening policy, campaigns and decision aid designs.